Poly(N-vinylcaprolactam) containing solid lipid polymer hybrid nanoparticles for controlled delivery of a hydrophilic drug gemcitabine hydrochloride - Surapaneni, Sai Geetika; Ambade, V. Ashootosh (RSC Advances, 2022)
Folic acid tagged and hydrophilic polymer containing solid lipid nanoparticles (SLNs) were formulated for the controlled and targeted delivery of gemcitabine, a hydrophilic drug. Drug loaded SLNs were prepared by double emulsion method and optimized by 3(2) level factorial design. Then, a hydrophilic polymer, namely, poly(N-vinylcaprolactam) (PVCL) was incorporated in the optimized SLN batch in the first aqueous phase (W1) to obtain solid lipid polymer hybrid nanoparticles (SLPHNs) that were further decorated with folic acid (F-SLPHNs). TEM analysis of SLNs and SLPHNs revealed the spherical shape with no aggregation while SLPHNs showed higher % EE. SLPHNs exhibited limited burst release of gemcitabine compared to SLNs as well as lower overall % release. All the formulations showed good cytocompatibility against MDA-MB-231 cell lines and folic acid-tagged hybrid particles (F-SLPHNs) showed remarkably higher cellular uptake.

Photo and pH dual stimuli-responsive block copolymer micelles with defined incorporation of o-nitrobenzyl units in poly(ε-caprolactone) ε-caprolactone) block for controlled release - Avhad, V. Shankarrao; Choudhari, Shakeb N.; Ambade, V. Ashootosh (European Polymer Journal, 2024)
A series of dual stimuli-responsive block copolymers with varying content of photocleavable o-nitrobenzyl (ONB) ester group pendent in the hydrophobic poly(epsilon-caprolactone) block and pH-cleavable acetal linkage at the junction with hydrophilic poly(ethylene glycol) block is synthesized. The hydrophobic block is a random copolymer synthesized by ring-opening copolymerization of epsilon-caprolactone and ONB-substituted epsilon-caprolactone containing varying compositions of the two monomers. Kinetics of polymerization shows that ONBfunctionalized monomer has lower reactivity than that of the unsubstituted monomer. The series of block copolymers shows self-assembly into well-defined spherical micelles of average size of 150-200 nm in aqueous solution. Photocleavage of ONB groups is studied by NMR and UV-vis spectroscopy, and its extent is determined. The two stimuli viz. . UV light and pH are used individually as well as simultaneously to study the controlled release of the encapsulated drug Camptothecin and the synergistic effect of the two stimuli is demonstrated. The effect of varying content of ONB groups is observed on drug release profile. MTT assay showed non-cytotoxic nature of the polymer. Cell uptake and photoinduced release of doxorubicin (DOX) from the micelles in MDAMB-231 cells is demonstrated.
Keywords: drug delivery; micelles; O-nitrobenzyl; pH-responsive; Photoresponsive; Poly(epsilon-caprolactone)

Methoxyl-containing hyper-crosslinked polymer from largely bio-based biphenyl methyl ether and its application in lithium-sulfur battery - Wale, Apparav K.; Das, Anoushka K.; Patil, Nita R.; Shelke, V. Manjusha; Ambade, V. Ashootosh; Wadgaonkar, Prakash P. (Reactive & Functional Polymers, 2025)
A new biphenyl methyl ether viz 2,2 `,3,3 `-tetramethoxy-5,5 `-bis(methoxymethyl)-1,1 `-biphenyl (TBMB) was synthesized starting from vanillin via three-step reaction sequence. The self-polycondensation of TBMB by employing two Bronsted acid catalysts, viz, p- toluenesulfonic acid (PTSA) and trifluoromethanesulfonic acid (TFSA) led to the formation of organic hyper-crosslinked polymers (HCPs) containing built-in methoxyl groups. HCPs were characterized by FTIR, solid state 13 C NMR, XPS, XRD, TGA, BET, and FESEM analysis techniques. HCPs synthesized using PTSA (HCP-PTSA) and TFSA (HCP-TFSA) exhibited a Brunauer-Emmett-Teller (BET) surface area of 480 +/- 5 and 590 +/- 4 m2/g, respectively and consisted of hierarchical pore structures with both micropores and mesopores. HCP-TFSA was evaluated as an active coating layer on conventional polypropylene (PP) separator in lithium-sulfur batteries to suppress the polysulfide shuttling on account of the ability of methoxyl groups to anchor soluble polysulfide species via coordination. The significant polysulfide adsorption capacity and improved cycling stability with a capacity of 617.2 mAh g- 1 at 0.5C and 99% capacity retention highlighted the potential of porous HCP containing built-in methoxyl groups in the development of attractive lithium-sulfur battery systems.
Keywords: Active coating layer; bio-based; Biphenyl methyl ether; Hyper-crosslinked polymer; lithium-sulfur battery; Methoxyl groups; Self-polycondensation

Sustained release polyurethane microcapsules by interfacial polycondensation using aromatic diols - Yadav, Prashant; Ravikumar, Aniruddha; Ambade, V. Ashootosh; Shanmuganathan, Kadhiravan (Reactive & Functional Polymers, 2025)
Polyurea-urethane (PUU) microcapsules prepared via interfacial polymerization have gained significant interest due to their tunable size and membrane thickness, high loading efficiency, and scalability. Although several aromatic and aliphatic diols and polyols have been used to produce PU foams and films, the use of aromatic diols to synthesize PUU MICs via interfacial polymerization is an unexplored domain due to the restricted solubility of aromatic diols in water. This report highlights the successful preparation of PUU microcapsules using an aromatic diol (benzene-1,4-dimethanol, BDM) to encapsulate dimethyl phthalate (DMP), a model insect repellent. The developed PUU microcapsules exhibited a high % encapsulation efficiency of 92 % and a size range of 1-20 mu m. Differential scanning calorimetry (DSC) thermograms revealed a significantly high glass transition temperature (Tg) of 143 degrees C as compared to 108 degrees C in the case of PUU MICs with aliphatic diols. Release studies confirm enhanced barrier properties for aromatic diol-based MICs as compared to aliphatic ethylene glycol-based PUU MICs, and interpretation of the release profile using the Weibull Model reveals that Fickian diffusion is the dominant mechanism in the release of DMP. These microcapsules can be used in high-performance applications such as composites, coatings, electronics, and construction.
Keywords: interfacial polymerization; Microencapsulation; polyurethane; sustained release